Program Inovasi Bisnis dan Adaptasi Perilaku Masyarakat Terkait Covid-19 Dalam Kehidupan Sehari-Hari Di Desa Alenangka Kecamatan Sinjai Selatan Kabupaten Sinjai - Hidayat, Taufik (Abdi Techno, 2021)
Community service programs are the practice of science, technology and art (IPTEKS) institutionalized by higher education through direct scientific methods to people who need to succeed in development and human development. Thematic KKN based on Problem Solving to solve problems with certain themes so that student activities are focused on solving certain problems and to achieve certain targets. One of them is the 105th Thematic KKN "Behavior Change Ambassador for Covid-19 Prevention and Participatory Oversight in the 2020 Pilkada". The Covid-19 thematic Real Work Lecture (KKN) is a Community Service Program to form awareness in empowering and educating the public to prevent the spread of Coronavirus Disease 19 (Covid 19) while adhering to the Covid-19 health protocol, namely maintaining physical distancing and wearing masks . Students who take part in the KKN program are guided by KKN Pengampuh Lecturers (DPK) who process mentoring and monitoring using an online system. This service program through Thematic KKN is carried out using the during and offline service methods. The KKN program is carried out in Alenangka Village, which is the area of ​​origin of students and this is done to minimize the spread of Covid-19. Work programs have produced several awards, including videos of public business innovations, and posters about Covid-19. On the other hand, there is an increase in community compliance with health protocols by always using a mask when leaving the house.